Bioremediation of Soils Polluted with Phenanthrene and Anthracene Using Ground Treatment Method and Chicken Manure as a Cosubstrate - Mohammad Mehdi Amin; Pegah Salehi; Fahimeh Teimouri; Tayebe Kalteh (Journal of Environmental Health and Sustainable Development, 2017)
Introduction: Bioremediation convertssoils pollutants to safe and non-toxic substance through metabolic activities of microorganisms. This research was conducted to evaluate the effect of bacteria on removal of phenanthrene and anthracene from polluted soils using chicken manure as an auxiliary substrate. Materials and Methods: First, uniformly-graded soils were transferred to the pilots, then activated sludge and chicken manure were added and mixed with the soilin specific ratios of 2:1 and 1: 1. Thereafter, phenanthrene and anthracene were manually added to the soil of each pilotat a rate of 12 mg/kg of soil. Anthracene and phenanthrene were measured using HPLC. Results: The results showed that in control pilots (without chicken manure and sludge), the removal percentage of pollutants (phenanthrene + anthracene) was 15%. Nevertheless, when chicken manure and chicken manure + sludge were used, the removal percentageincreased to 80 and 84%, respectively. Control pilots showed the lowest percentage of COD removal and varied from approximately 7 to 10%. Although the percentage of COD removal was approximately 80%, with the addition of chicken manure + sludge, COD removal rate reached 90% (the highest removal percentage). Conclusion: The use of chicken manure as a cosubstratecanbe considered as an appropriate alternative for increasing the efficiency of bioremediation of oil compounds in soil.